The risks of deterioration of documentary heritage in Latin America - Fernández, Mario Omar (2008)
This document narrates the risks of deterioration to which documentary heritage is exposed in Latin America, it refers to geological phenomena, hydrometeorological, risks resulting from human action and environmental. Subsequently the author offers his final considerations and how preventive conservation has become the only way to safeguard the historical memory of each of the nations.